Scientists Discover New Adaptation to Oxygen-Poor Air at High Altitudes - Graham, S. (2002)
Visitors to high-elevation locales often experience difficulty breathing because the amount of oxygen available in the atmosphere decreases with increasing altitude. In extreme situations, altitude sickness can be fatal. But people born and raised at high altitudes function well despite the reduced availability of oxygen. New findings published online this week by the Proceedings of the National Academy of Sciences, suggest that residents of a high-altitude village in Ethiopia have a unique way of adapting to the lower levels of oxygen at high elevations. Previous research had suggested two ways that humans may adjust to lower oxygen levels. Both methods involve hemoglobin, a protein in red blood cells that binds to oxygen and carries it throughout the body. Members of a well-studied group living the Andes, for example, have more hemoglobin than do people who live at sea level. Natives of the Tibetan plateau, in contrast, have similar hemoglobin levels as their low-living counterparts, but a greater percentage of the protein binds to oxygen molecules in the blood. Cynthia M. Beall of Case Western Reserve University and her colleagues studied 313 native residents of the Ambaras Region of the Semien Mountains National Park in Ethiopia, situated 3,530 meters above sea level. Surprisingly, the subjects not only had hemoglobin levels similar to those seen in sea level populations but they also displayed comparable rates of binding between oxygen and hemoglobin. The authors posit that the Ethiopian population represents a third method of adaptation to high-altitude oxygen deprivation, although the underlying biological mechanisms remain unknown. Learning why the three populations differ, they conclude, will require further investigation.